Awareness of parental illness: a grounded theory of upholding family equilibrium in parents on long-term sick-leave in primary health care - Charlotte Oja; Tobias Edbom; Anna Nager; Jörgen Månsson; Solvig Ekblad (Taylor & Francis Group, 2021)
Objective To understand the main concern of chronically ill parents and how they resolve this concern in relation to their children. Design Grounded theory. Setting Three primary health care clinics in Sweden. Subjects Thirty-two interviewed parents and their children. Main outcome measures Processes and typologies of upholding family relationships. Results A concern of chronically ill parents is sustaining family equilibrium, achieved through a process of upholding family relationships. How a parent upholds depends upon his/her comprehension of the illness and of their child's need for parenting. In response to the parent's upholding behaviours, children mirror the effect of the illness to the parent, the child's specific behaviour depending on his/her level of comprehension regarding the parent's illness. Their combined behaviours create an awareness context that may be closed, concealed, suspicious, conflicted, mutual pretence or open. When the parent drives and facilitates the evolution of comprehension, the context quickly evolves from closed to open. When the parent hinders the process by masking and resisting the child responds by probing and proving and they become locked into a suspicious or conflicted awareness context with high relational tension. To create family equilibrium the parent needs to reveal and facilitate the awareness process. Conclusion Parents on long-term sick leave in primary health care can need assistance to facilitate the awareness context of themselves and their child. Implications: Clinicians can identify the current awareness context of their patient and help their patient towards increased understanding of their illness; their child's needs and the parental capacities needed to reveal the illness and its impacts.Key Points Children are affected when parents are ill; they wish for information on their parent's illness. Effective interventions are available in settings other than primary health care and possibilities seen by GPs and families in Scandinavian primary health care have been previously described. There is a knowledge gap in how parents view themselves and their parenting when ill in primary health care. An analysis grounded in interviews was needed to generate a hypothesis (theory) of parental concerns and behaviours. This theory proposes that an important concern of chronically ill parents is to sustain family equilibrium, which they attempt to do by upholding family relationships. Specific upholding behaviours include masking, resisting, colluding, and revealing. In response, children will engage in mirroring behaviours. Which paired behaviours are enacted will depend upon the respective levels of comprehension of parent and child regarding the illness and on the child's need for parenting. In their interactions, parent and child create one of six awareness contexts. Identifying the current awareness context in the family about chronic parental illness provides clinicians with a conceptual tool to better support those families locked in suspicious or conflicted awareness contexts.